2023
DOI: 10.3390/plants12051144
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Taxonomically Challenging Hexaploid Alpine Shrub Willows of Salix Sections Phylicifoliae and Nigricantes (Salicaceae)

Abstract: The complex genomic composition of allopolyploid plants leads to morphologically diverse species. The traditional taxonomical treatment of the medium-sized, hexaploid shrub willows distributed in the Alps is difficult based on their variable morphological characters. In this study, RAD sequencing data, infrared-spectroscopy, and morphometric data are used to analyze the phylogenetic relationships of the hexaploid species of the sections Nigricantes and Phylicifoliae in a phylogenetic framework of 45 Eurasian S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…turned out to be confused with S. phylicifolia L. (Fig. 1B; see also [35]). Both species are medium-sized shrubs and occur in the subalpine zone.…”
Section: Study Speciesmentioning
confidence: 97%
“…turned out to be confused with S. phylicifolia L. (Fig. 1B; see also [35]). Both species are medium-sized shrubs and occur in the subalpine zone.…”
Section: Study Speciesmentioning
confidence: 97%
“…The observed diversity in ploidy levels in North American willows, sometimes within species, has also been shown previously (Argus, 2010). The slightly lower number of polyploids in the EuA clade is biased by our reduced sampling for this clade with a focus on diploids (but see Wagner et al, 2020Wagner et al, , 2023. Presumably, 40% of willow species are polyploid (Suda and Argus, 1968) and have a base chromosome number of x = 19 (Argus, 1997).…”
Section: Polyploidization and Hybridizationmentioning
confidence: 98%
“…In a recent Populus L. and Salix study employing a target capture data set on a broad sampling, Sanderson et al (2023) revealed that high amounts of ancestral hybridization resulted in conflicting phylogenetic signals, especially in genus Salix. RAD sequencing (Baird et al, 2008) was recently used to overcome the lack of phylogenetic information within the Chamaetia/Vetrix clade (Gramlich et al, 2018;He et al, 2021;Wagner et al, 2018Wagner et al, , 2020Wagner et al, , 2023. Using this method, Wagner et al (2018) published the first well-resolved phylogeny of diploid European members of the Chamaetia/Vetrix clade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyploidy is an important phenomenon in understanding the biogeography and taxonomy of disjunct arctic–alpine species complexes. Wagner et al [ 8 ] provided detailed insights into taxonomically challenging hexaploid alpine shrub willows ( Salix sp., Salicaceae ). In this study, RAD sequencing data, infrared spectroscopy, and morphometric data were used to analyze the phylogenetic relationships of the species from the Phylicifoliae and Nigricantes sections in a framework of 45 Eurasian Salix species.…”
mentioning
confidence: 99%